Electric circuits - Nilsson, James William; Riedel, Susan A. (Upper Saddle River, N.J. : Prentice Hall, 2001)
Foundation Title. Electric Circuits is the most widely used introductory circuits textbook of the past decade. The book has remained popular due to its success in implementing three themes throughout the text: (1) It builds an understanding of concepts based on information the student has previously learned; (2) The text helps stress the relationship between conceptual understanding and problem-solving approaches; (3) The authors provide numerous examples and problems that use realistic values and situations to give students a strong foundation of engineering practice.
Includes index.
Keywords: Electric circuits